THE NUMERICAL THREE-DIMENSIONAL HYDRODYNAMIC SIMULATION OF COLLIDING STELLAR WINDS IN A CLOSE BINARY SYSTEM - Nazarenko, V. V.; Glazunova, L. V.; Nazarenko, S. V. (Одеські астрономічні публікації, 2013)
In the present numerical study the stellar winds from both supergiant-components of a detached close binary system (CBS) are simulated applying methods of the three-dimensional numerical hydrodynamics. The simulated winds collide in the space between the components, forming a stationary shock wave. That shock wave has geometrically intricate shape that consists of several separate ﬁlamentary structures. The temperature in the shock wave is about 105K, and the temperature in the space adjacent to the shock wave is around104 – 1,5 ∙ 104K. Away from the line-of-centres the shock wave is curved due to the eﬀect of the Coriolis force sand greatly expands under the gas pressure at that. At a distance of about two orbital separations from the line-of-centres the shock wave expands so much that it is practically smearing out in space.